2020
DOI: 10.1371/journal.pone.0230285
|View full text |Cite
|
Sign up to set email alerts
|

High sPLA2-IIA level is associated with eicosanoid metabolism in patients with bacterial sepsis syndrome

Abstract: The aim of this study was to determine the association between secretory phospholipase A2 group IIA (sPLA2-IIA) and eicosanoid pathway metabolites in patients with bacterial sepsis syndrome (BSS). Levels of sPLA2-IIA, eicosanoids prostaglandin (PG)E2, PGD synthase were quantified in the sera from patients confirmed to have bacterial sepsis (BS; N = 45), bacterial severe sepsis/septic shock (BSS/SS; N = 35) and healthy subjects (N = 45). Cyclooxygenase (COX)-1 and COX-2 activities were analyzed from cell lysate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 61 publications
(84 reference statements)
0
9
0
Order By: Relevance
“…Serum levels of the prostaglandins PGE 2 and PGD 2 are almost doubled in human sepsis subjects. This elevated AA-derived eicosanoid production in human sepsis is accompanied by increased secretory PLA 2 group IIA and COX-2 activity (25).…”
Section: Eicosanoids and Specialized Pro-resolving Mediatorsmentioning
confidence: 91%
“…Serum levels of the prostaglandins PGE 2 and PGD 2 are almost doubled in human sepsis subjects. This elevated AA-derived eicosanoid production in human sepsis is accompanied by increased secretory PLA 2 group IIA and COX-2 activity (25).…”
Section: Eicosanoids and Specialized Pro-resolving Mediatorsmentioning
confidence: 91%
“…The circulating levels of sPLA 2 -IIA are very low in healthy conditions but increase significantly during inflammation or infection [13,14]. Several studies have highlighted the role of sPLA 2 -IIA as a biomarker in sepsis and various infections [14][15][16]. sPLA 2 -IIA is also well-recognized for its antimicrobial role, especially toward gram-positive bacteria since it can directly hydrolyze the membranes of these organisms, which are enriched in PG and PE, the preferred substrates for this specific isoform [17].…”
Section: Role Of Spla 2 Group Iia and Iid In Alimentioning
confidence: 99%
“…Investigations into the biological role of mammalian group IIA PLA 2 , also known as inflammatory PLA 2 , in the development of several pathologies of inflammatory and immunological origin have been described. Several studies have revealed that group IIA sPLA 2 s are present in high levels in rheumatoid arthritis [47][48][49][50], acute pancreatitis [51][52][53], septic shock [54,55], Crohn's disease and ulcerative colitis [56][57][58], respiratory distress syndrome [59][60][61], bronchial asthma and allergic rhinitis [59,62], atherosclerosis [63,64], autoimmune diseases [65], and cancer [66][67][68][69]. These observations imply that both local and systemic inflammation are associated with the release of sPLA 2 s in vivo, thus raising the unclear question of the role of these PLA 2 s in inflammatory reactions.…”
Section: Phospholipases Amentioning
confidence: 99%